Consequences of lighting programme in rearing phase and its effects on amino acid requirements in a broiler breeders flock in egg production - Ferreira, Nayara Tavares [UNESP]; Sakomura, Nilva Kazue [UNESP]; Gous, Robert Mervyn (Elsevier, 2019)
The aim of this study was to model the changes in the egg production and requirements of broiler breeder hens flock, in response to different lighting programmes during the rearing period. The growth of each individual in a population up to the time when its first egg is laid was simulated and then averaged to obtain the mean response of the population to different lighting programmes. The information about the age, body weight and body composition over the growth period are required in order to determine the amino acid requirements of broiler breeder hens until sexual maturity (egg-laying period), the age at first egg (AFE) and egg production. Were used equations to estimate body, feather, ovary, oviduct and compositions of these parts, as a function of age. Also was estimated AFE and EP according to the lighting programmes: Constant daylengths during rearing: 8, 10, 12, 14, 16, 18 h and Single increment from 8 to 16 h at 8, 10, 12, 14, 16, 18 and 20 weeks of age. It is important to point out the greater differences in the requirements until all the broiler breeders begin laying the egg. For 24 weeks of age, the requirements may vary 329–602 mg/bird/day of Lys, 258–550 mg/bird/day of Met + Cys and 180–392 mg/bird/day Thr. For 28 weeks of age, the requirements range 362–922 for Lys; 303–830 for Met + Cys and 213–599 for Thr. For 32 weeks of age, the requirements range 824–982; 711–888; 514–644 mg/bird/day for Lys, Met + Cys and Thr, respectively. Knowing the requirements helps to establish the best nutritional program, and optimize feeding without excesses and deficiencies. These results support the view that a modelling approach has the potential to help nutritionists to make decisions about feeding broiler breeder flocks more efficiently.
Keywords: Laying period; Prediction equation; Simulation; Stochastic model